2021
DOI: 10.1055/s-0041-1729876
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Factors Affecting Outcomes in Scalp Replantation: A Systematic Review of the Literature

Abstract: Introduction Replantation is the ideal treatment in traumatic scalp defects to provide immediate coverage with restoration of hair-bearing skin. However, data are limited to case reports and small case series. Comprehensive analysis of techniques and outcomes is not available. Our aim was to systematically analyze the available literature to better understand management and postoperative outcomes of patients undergoing scalp replantation. Methods A systematic review of the PubMed, Cochrane, and EBSCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 81 publications
1
6
0
Order By: Relevance
“…In our study, 3 patients presented with partial occipital scalp necrosis postoperatively, which was in agreement with a previous meta-analysis that most necrotic areas following avulsed scalp replantation occurred in the occipital region. 18 Some studies have suggested that the occipital scalp is more prone to necrosis owing to poorer blood perfusion, which is further aggravated by the patient being supine for a long time after the injury. 7 The tight connection between the occipital scalp layers may also play a role in postoperative occipital scalp necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 3 patients presented with partial occipital scalp necrosis postoperatively, which was in agreement with a previous meta-analysis that most necrotic areas following avulsed scalp replantation occurred in the occipital region. 18 Some studies have suggested that the occipital scalp is more prone to necrosis owing to poorer blood perfusion, which is further aggravated by the patient being supine for a long time after the injury. 7 The tight connection between the occipital scalp layers may also play a role in postoperative occipital scalp necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Unique situations such as traumatic scalp avulsions should be addressed primarily with an evaluation for attempted replantation or revascularization. 37 However, in most other cases where scalp reconstruction is indicated, we believe that local factors such as presence of radiation or a moderate-to-severe local scar burden must be addressed by recruiting healthy distant tissue. 4 38 39 The complex factors associated with scalp wounds include margin-positivity in cases of tumor, presence of neoadjuvant radiation, as well as prior attempts at local scalp rearrangement.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Historically, scalp replantation is typically achieved using bilateral STAs (95%) on a single-piece scalp flap (91%). 25 However, replantation of the total scalp via a single STA has been previously reported with good outcomes. [26][27][28] In this cadaveric study, osteocutaneous flaps were entirely perfused via a single STA pedicle, suggesting that skull perfusion territories mirror those of the scalp.…”
Section: Perfusion Territory Of the Superficial Temporal Arterymentioning
confidence: 99%